Problematika Regulasi Pengelolaan Dana Abadi Umat: Disharmonisasi Kelembagaan dan Legal Standing - Muhammad Aziz Zakiruddin (Sharia and Law Faculty, 2021)
Law Number 8 of 2019 concerning the Implementation of Hajj and Umrah Worship, discusses the polemic and disharmony of Law Number 34 of 2014 concerning Hajj Financial Management. The elimination and transfer of the functions and duties of the Badan Pengelola Dana Abadi Umat (BP-DAU) to the Ministry of Religion resulted in disharmony. Not only in the regulatory aspect but in institutions. Some questions or problem formulations that arise in this paper are, what are the dynamics in the management of the Umat Endowment Fund? Second, what are the factors of institutional disharmony and legal aspects in the management of the Dana Abadi Umat? How is the impact of this disharmony on the management of the Dana Abadi Umat? In answering these questions the authors use the Library research method with a statutory approach (Statue approach), which is built on legal theories, tiered legal theory